2017
DOI: 10.7717/peerj.3776
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of theMADS-boxtranscription factor family in pear (Pyrus bretschneideri) reveals evolution and functional divergence

Abstract: MADS-box transcription factors play significant roles in plant developmental processes such as floral organ conformation, flowering time, and fruit development. Pear (Pyrus), as the third-most crucial temperate fruit crop, has been fully sequenced. However, there is limited information about the MADS family and its functional divergence in pear. In this study, a total of 95 MADS-box genes were identified in the pear genome, and classified into two types by phylogenetic analysis. Type I MADS-box genes were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 154 publications
2
43
1
1
Order By: Relevance
“…Thus, these two gene types may be regulated by different mechanisms, with the more complex mechanisms controlling type II genes. A similar phenomenon was observed in A. thaliana , pear, and cucumber (Hu & Liu, ; Parenicova et al, ; Wang et al, ). Additionally, most type I genes were highly expressed in a single stage, whereas type II genes were usually expressed in successive developmental periods.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, these two gene types may be regulated by different mechanisms, with the more complex mechanisms controlling type II genes. A similar phenomenon was observed in A. thaliana , pear, and cucumber (Hu & Liu, ; Parenicova et al, ; Wang et al, ). Additionally, most type I genes were highly expressed in a single stage, whereas type II genes were usually expressed in successive developmental periods.…”
Section: Discussionsupporting
confidence: 77%
“…As shown in Figure 5, the expression of CsMADS26 was detected in the six tested tissues, with the highest levels in male flower and female flower, followed by fruit and leaf, and much lower levels in stem and root. CsMADS26 is mainly expressed in reproductive organs, which is in agreement with the profiles of other AGL15 subfamily genes in various plants, including Prunus mume (PmMADS30) [33], Vitis vinifera (VvMADS20 and VvMADS25) [34], P. bretschneideri (PbrMADS34 and PbrMADS37) [9], Z. jujuba (ZjMADS42 and ZjMADS45) [10], G. hirsutum (GhAGL15-3) [2], D. caryophyllus (DcaMADS22 and DcaMADS23) [12], and M. notabilis (MnMADS6) [7], indicating its important function in the development of reproductive organs. In addition, its expression was also observed in leaf, indicating that CsMADS26 might play a role in leaf development.…”
Section: Tissue Expression Profiles Of Csmads26 In Cucumbersupporting
confidence: 81%
“…As a result, CsMADS26 contains 55.86% alpha helices, 12.61% extended strands, 4.50% beta turns, and 27.03% random coils, respectively ( Figure 2). Previous reports have suggested that the K domain is mainly responsible for dimerization [2,9]. However, CsMADS26 possesses a large number of alpha helices in its K domain, suggesting that CsMADS26 may have a particular function in facilitating the dimerization of MADS-box proteins.…”
Section: Cloning and Sequence Analysis Of Csmads26mentioning
confidence: 96%
See 1 more Smart Citation
“…The involvement of MADS-box genes in anthocyanin accumulation have been reported in different species including Arabidopsis (Nesi et al 2002) and other Rosaceae fruit species such as bilberry (Jaakola et al 2010) and pear (Wang et al 2017). Among the four MADS box candidates expressed in fruit cortex, two of them ( gene26119 , gene06301 ) that are expressed at late stages of fruit development (Hawkins et al 2017) show a pattern of expression opposite to that of ANR, which makes them potential candidates for regulating ANR in strawberry fruit.…”
Section: Discussionmentioning
confidence: 99%